2014
DOI: 10.1111/jsm.12532
|View full text |Cite
|
Sign up to set email alerts
|

Orgasmic Dysfunction: Prevalence and Risk Factors from a Cohort of Young Females in Mexico

Abstract: Introduction Orgasmic dysfunction (OD) is defined as the inability to achieve an orgasm, markedly diminished intensity of orgasmic sensations, or marked delay of orgasm during any kind of sexual stimulation. OD definition and method of diagnosis vary widely across studies. Aim The aim of this study was to identify the prevalence and risk factors that predispose Mexican women to OD. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…Similar differences in the impact were discovered for parity, family income, employment, and partnership status. 23 In our study, we noted highly statistically significant association between sexual dysfunction and nulliparity, previous episiotomy, higher CS, circumcision and no contraception and vaginitis or cervicitis.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Similar differences in the impact were discovered for parity, family income, employment, and partnership status. 23 In our study, we noted highly statistically significant association between sexual dysfunction and nulliparity, previous episiotomy, higher CS, circumcision and no contraception and vaginitis or cervicitis.…”
Section: Discussionsupporting
confidence: 56%
“…According to Villeda Sandoval et al, 23 as women in their 30s gain greater self-awareness and ease embracing and expressing their sexuality, they may exhibit fewer dysfunctional symptoms. Similar differences in the impact were discovered for parity, family income, employment, and partnership status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies showed a U-shaped prevalence of sexual dysfunction, with younger and older women being most affected [ 113 ]. Women in their 30s may show fewer symptoms of dysfunction as they learn more about their preferences and become more comfortable accepting and expressing their sexuality [ 103 ]. Similar variation in the effect (whether positive or negative) was found for employment, income, partnership status, and parity.…”
Section: Discussionmentioning
confidence: 99%